2011
DOI: 10.4314/bajopas.v2i2.63756
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, caffeine and tannin analyses in some brands of tea consumed in Kano Metropolis, Nigeria

Abstract: The determination of proximate, caffeine and tannin contents of five different (China, Kenya, India, Srilanka and Mambilla) tea leaves samples sold in Kano markets was conducted. The moisture content was generally high in all the tea samples and ranged from 5.6% in Mambila to 7.5% in India samples. Ash content was relatively low and ranged between 4.90% in Srilanka to 7.20% in Mambila and Kenya samples respectively. Crude fibre ranged from 14.00% in China to 18.82% in Srilanka samples, while ether extract cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
2
9
1
Order By: Relevance
“…There were significant (p<0.05) differences between the crude fibre content of all the samples. The powdered Moringa leaves had the highest crude fibre content (18.64%), which is in agreement with the crude fiber content (18.82%) reported for Srilanka tea (Mohammed and Sulaiman, 2009), while the fresh leaf had 1.09% crude fibre content. Crude fibre stimulates the movement of the bowel and helps to prevent constipation (Okanlawon, 2000).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…There were significant (p<0.05) differences between the crude fibre content of all the samples. The powdered Moringa leaves had the highest crude fibre content (18.64%), which is in agreement with the crude fiber content (18.82%) reported for Srilanka tea (Mohammed and Sulaiman, 2009), while the fresh leaf had 1.09% crude fibre content. Crude fibre stimulates the movement of the bowel and helps to prevent constipation (Okanlawon, 2000).…”
Section: Resultssupporting
confidence: 87%
“…The result revealed that black tea had the highest concentration of all the minerals compared to other samples, which could be attributed to the high percentage of ash present. Black Moringa leaf tea also had the highest ash content (Table 1), which is in agreement with the observation of Mohammed and Sulaiman (2009) that high content of ash is an indication of a good source of minerals. The production processes of black tea that involves withering which reduces moisture content of fresh leaf to one third (Jabeen et al, 2015), helps to reduce loss of juice during maceration that aids enzymatic oxidation process called fermentation (Hsu et al, 2011) and subsequently enhanced mineral retention compared to green tea.…”
Section: Mineral Composition Of Moringa Leaf Tea Samples Fresh and Psupporting
confidence: 90%
See 3 more Smart Citations